Vaccination: influencing factors and view from an Islamic perspective - E. Zainudin, Engku Nuraishah Huda; Mohammad, Khairool Azizul; Aris, Athirah; Shahdan, Intan Azura (IIUM Press, 2018)
Vaccine refusing and hesitant among parents has created a delicate issue for the health care providers because of its sensitivity in cultural differences, educational backgrounds and to a certain extent, politically motivated. Vaccination, which is an important intervention, correlates well with the priorities of Islamic jurisprudence (Maqasid al-Shariah); that states the preservation of life comes second after the preservation of Deen (religion). From the Islamic point of view, life is a gift from Allah Subhanahu wa Ta’ala (SWT; the Most Glorified, the Most High) and its protection and continuation is of greatest value and need. Aims: This brief article has the objective to firstly, investigate factors that influence vaccination, and secondly, understand the Islamic perspective on vaccination. Methodology: Relevant literatures were reviewed based on a combination of one or more of the following keywords: vaccine, vaccination decision, vaccine hesitancy, factors influencing vaccine, vaccine impact, Islamic perspective and Muslims practice. An Islamic perspective on vaccination was extracted using the primary sources (related Qur’anic verses and Hadith) as well as secondary sources (fatwa; Islamic jurisprudence, made by Islamic scholars). Lastly, the current available Shariah rulings on vaccination and the related principles involved were analyzed. Conclusion: The main outcome of this review would allow various parties. i.e. the community, health scientists, medical practitioners and vaccine manufacturers, to be cognizant in both earlier and recent Shariah rulings pertaining vaccination.